Development of use lab website for user science and engineering laboratory (use lab) / Nur Asyikin Mohd Zamberi - Mohd Zamberi, Nur Asyikin (2010)
User Science and Engineering Laboratory (USE Lab) of UiTM Shah Alam is a new high cost laboratory built for the purpose of usability testing research and project. The attention received by this lab is still less by looking at the few numbers of projects done. Hence, this research needs to be conducted as an effort to attract people who are interested in the area of usability practices to gain more information of services and facilities offered at this USE Lab. The main purpose of this research is to give opportunities on the USE Lab to promote their services through a website. For this reason, this research focuses on the design issues of developing the USE Lab website. The objectives of this research are to identify the contents of USE Lab website and to analyze the User Interface (UI) Design that will be applied in developing the USE Lab website. The achievement of these objectives is based on the reviewed done on 10 selected usability laboratory websites and from the literatures review on journals, articles, and books. The results from the comparison on those websites will be considered to be used in the design based on the guidelines from reading the journals and understanding the literatures review. Overall, this research had contributed in producing the USE Lab website for User Science and Engineering Laboratory of UiTM Shah Alam.